O processo de enfermagem em sistemas informatizados no Brasil - Gomes, João Júnior (2010)
This study aimed to analyze the publishing material about the nursing process in computer systems in Brazil, identifying the theoretical references in nursing, health attention level, and nursing classification system through an integrative review on the literature about it. For this purpose two data basis (LILACS e PubMed) have been used, besides a virtual library (Cochrane). The sample has been constituted of 13 studies. The data have demonstrated that 46,2% of the mentioned studies have used the theoretical reference of Basic Human Needs, from Horta, 15,4% have used eclectically conceptual models, 7,7% the human thought cognitive theory and 30,7% have not mentioned any. Concerning to the health attention level, 76,9% have been identified as directed to the high complexity level and 23,1% to the nursing teaching. The use of CIPE® have occurred in 15,3% of the studies; the classification on NANDA-I, NIC, NOC systems in 15,3 %; the classification on NANDA-I and NIC, in 7,7%; the classification on NANDA-I, 23,1% and 38,6% have not mentioned the use of any classifications. Through the results of this study one could notice the existence of difficulties in the development and in the evaluation of the technological tool for implementing the nursing process, although there have been positive contributions reflecting on the improvement of the praxis and on teaching. On the other side, it is possible to name a concerning on behalf of the authors about the need on software improvement. It is expected that this study may unchain, on the assistant nurses and researchers, a process of reflecting on the importance of developing technical tools on implementing the nurse process on the basic attention, based on theoretical reference and nursing classifications.